The Application of Role Play Technique In Improving The Second Year Office Administration Students’ Speaking Ability of SMK N 1 Pekanbaru - Oktariani, Falinda Oktariani; ', Mahdum; ', Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This pre-experimental design was aimed to find out if the application of role play technique is effective in the speaking ability. The reasons for conducting this research because of several problems: the teachers did not use English frequently and they still used monotonous way of class discussion focusing on text book, and furthermore, the lack of ideas became the other reason of the difficulties faced by the students when the teacher gave them a topic to be explored in spoken form. The participants were 37 studentsof the second year office administration students of SMK N 1 Pekanbaru. The time of the research was on academic 2013/2014, from April to June at the second semester.The data was collected by using of pretest and posttest. The data were assessed by the three raters and analyzed by using of SPSS Application. The research finding showed that  the implementation of applying role play as the teaching technique was effective to  improve students’ speaking ability. The finding also proved that in the pretest students’ average score was only 58.49 and it improved to 74.16 in the posttest.In addition, applying role play as a teaching technique in English language teaching and learning could also improve students’ ability to speak English in terms of grammar, vocabulary, pronunciation, fluency, and comprehension.   Keywords:Role play technique, Students’ speaking Ability